Facebook and education: students' privacy concerns - Al-Dheleai, Yahya Mohammed (Canadian Center of Science and Education, 2015)
In this article, the focus is on students' privacy concern towards the use of Facebook for educational purpose. The authors of this article discussed the issue based on the findings of the previous studies. The review of the literature showed that students are more concerned about invading their privacy when interacting with their professors via Facebook. Authors of this article provided recommendations that can help faculty to tackle students concerns about their privacy. Additionally, provided recommendations may facilitate educational use of Facebook in higher education